Implementation of Business Process Mapping Framework for Indonesia’s Government Institutions - Martinus Tukiran; Nugraheni Puspita Sari; Lukas Danny Tjitrabudi; Nurul Amalia (Universitas Muhammadiyah Yogyakarta, 2022)
Government organizations today face unprecedented challenges in carrying out their vital mission and in an environment marked by shrinking budgets, strict regulations, and changing workforce status. The business process map is a diagram that shows the working relationship between organizational units that generate added value to all respective stakeholders. While there is some independent guidance available on how various tools support different aspects of business process mapping initiatives, organizations still need to determine what their speciﬁc needs are and be able to establish how information gathered on tool functionality can be evaluated against these needs. This study will explore the practices of implementation business process mapping in 10 government institutions in Indonesia using 3-dimentional framework approach. The research employed a qualitative approach with in-depth interviews, observation, and study documents were performed for collecting and analysis data. The framework was succeeding to describe a paradigm shifting to encourage people move from a silo thinking to cross function team. Finally, business process map as a foundation of organizational bureaucracy movement shows an improvement in institutional capacity to encourage administrator in operational consistency.